El crítico como escritor. Ángel Rama y sus compañeros de la diáspora - Bernabé, Mónica (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2006)
From metaphors such as "lettered city", "lettered" and "masked ball", through which Ángel Rama develops relevant notions in his posthumous books The lettered city and The democratic masks of modernism, the work retrieves the image of the critic and the autobiographical profile of his essays. Links between these notions and the writing of Diary will make it possible to appreciate the subjective plot projected onto the critical works.